2020
DOI: 10.1101/2020.02.26.966143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artesunate interacts with Vitamin D receptor to reverse mouse model of sepsis-induced immunosuppression via enhancing autophagy

Abstract: Background and PurposeImmunosuppression is the predominant cause of mortality for sepsis due to failure to eradicate invading pathogens. Unfortunately, no effective and specific drugs capable of reversing immunosuppression are available for clinical use. Increasing evidence implicates vitamin D receptor (VDR) involved in sepsis-induced immunosuppression. Herein, artesunate (AS) was discovered to reverse sepsis-induced immunosuppression and its molecular mechanism is investigated.Experimental ApproachEffect of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In theory, it is reliably to investigate immunomodulatory agents to improve immune functions based on the molecular mechanism of the immunosuppression of GCs ( Cain and Cidlowski, 2017 ). Previously, in our lab AS was found not only inhibit excessive inflammation during sepsis ( Kuang et al, 2018 ) but also possess an immunomodulatory effect on CLP-induced immunosuppression mice ( Shang et al, 2020 ). Herein, in HC mice, our results further demonstrated AS has a significant protective effect on HC mice via increasing pro-inflammatory cytokines release and enhancing bacterial clearance, suggesting AS is indeed a bidirectional immunomodulator, which is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, it is reliably to investigate immunomodulatory agents to improve immune functions based on the molecular mechanism of the immunosuppression of GCs ( Cain and Cidlowski, 2017 ). Previously, in our lab AS was found not only inhibit excessive inflammation during sepsis ( Kuang et al, 2018 ) but also possess an immunomodulatory effect on CLP-induced immunosuppression mice ( Shang et al, 2020 ). Herein, in HC mice, our results further demonstrated AS has a significant protective effect on HC mice via increasing pro-inflammatory cytokines release and enhancing bacterial clearance, suggesting AS is indeed a bidirectional immunomodulator, which is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate (AS), an anti-malarial drug, has been discovered to possess an immunomodulatory effect on cecum ligation and puncture (CLP)-induced immunosuppression mice ( Shang et al, 2020 ). However, it is unclear whether AS has potent regulation on GCs-induced immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate could restore Unc-51-like autophagy-activated kinase 1-(ULK1-) mediated autophagy, reverse LPS tolerance, and relieve the immunosuppression of macrophages induced by sepsis. The interference of the CaMKII-IP3R-CaMKKβ pathway [20] and the activation of vitamin D receptor [21] were found involved in the process.…”
Section: Inhibition Of Baff Expression and Autoantibody Generation [5...mentioning
confidence: 97%
“…The neutrophil counts were significantly increased in the blood of mice exposed to low-dose artesunate (8 mg/kg/d) for 45 days [12], suggesting the effect of artesunate on neutrophils is in an immune state-, dosage-, and time-dependent manner, whose specific mechanism remains to be investigated in the future. [8,9] Reduction of proinflammatory cytokines [9] Inhibition of chemotaxis [10] Promotion of oxidative response with infection [11] Promotion of counts with low dose for long time [12] Nrf2 signaling pathway [8] Monoarthritis [7] Allergic asthma [8] Septic lung injury [9] Monocytes/ macrophages Reduction of proinflammatory cytokines [13][14][15][16] Reduction of MMP-9 [17] Reduction of NO [18] Inhibition of autophagic activation [19] Promotion of LPS internalization [16] Restoration of autophagy and reversing LPS tolerance in sepsis [20,21] Activation of vitamin D receptor [21] NF-κB pathway [13][14][15]17] cAMP-mediated pathway [18] Wnt/β-catenin pathway [18] TRAF6-Beclinl-PI3KC3 pathway [19] CaMKII-IP3R-CaMKKβ pathway [20] Sepsis [13,14,16,17,20,21] Colitis [15] NK cells Promotion of cytotoxic activity against tumor cells [22][23][24][25]…”
Section: Artesunate and Innate Immune Cellsmentioning
confidence: 99%
“…Whereas the vast majority of investigations reported on the immunosuppressive effects of artemisinin-type drugs, there are also some studies that observed an increase of immune function, for example, by the inhibitory activity against Treg cells, the recovery of the Th1/Th2 balance, and so on. [243][244][245][246][247] This might be beneficial in cancer treatment, but counterproductive to treat inflammatory and autoimmune diseases. Here, immunosuppressive rather than immune-stimulating effects are required.…”
Section: Synopsis Of Data and Future Perspectivesmentioning
confidence: 99%